2016
DOI: 10.12998/wjcc.v4.i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment ofHelicobacter pyloriinfection: Current and future insights

Abstract: Helicobacter pylori (H. pylori) is an important major cause of peptic ulcer disease and gastric malignancies such as mucosa-associated lymphoid tissue lymphoma and gastric adenocarcinoma worldwide. H. pylori treatment still remains a challenge, since many determinants for successful therapy are involved such as individual primary or secondary antibiotics resistance, mucosal drug concentration, patient compliance, side-effect profile and cost. While no new drug has been developed, current therapy still relies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 135 publications
2
92
0
4
Order By: Relevance
“…However, the prevalence of the infection varies between developed and developing countries. A higher prevalence of H. pylori infection (75% -83%) was found in Latin American countries than in Japan (40%) and other developed countries [1] [2].…”
Section: Introductionmentioning
confidence: 87%
“…However, the prevalence of the infection varies between developed and developing countries. A higher prevalence of H. pylori infection (75% -83%) was found in Latin American countries than in Japan (40%) and other developed countries [1] [2].…”
Section: Introductionmentioning
confidence: 87%
“…Additionally, cranberries and their bioactive constituents modulate bacterial adhesion, coaggregation and biofilm formation which may in turn reduce gastrointestinal and urinary tract infections and serve to reduce systemic inflammation (42). Cranberries have also shown efficacy against Helicobacter pylori ( H. pylori ), a Gram-negative bacterium linked to peptic ulcer disease, gastric carcinoma and lymphoid tissue lymphoma (44, 45). …”
Section: Chemoprevention Of Aerodigestive Tract Cancers By Berriesmentioning
confidence: 99%
“…Amoxicillin is more effective than other drugs due to low resistance rate and high pH environment. Some studies demonstrated that high-dose a PPI plus amoxicillin is overcoming resistance rate and their eradication rate is 72 -81% (Safavi et al, 2016;Vaira et al, 2009). Recently, studies found that it is highly eradicating of H. pylori infection compared to first line therapy; after it cannot achieve in therapeutic efficacy treatment of this infection due to antibiotic bacterial resistance smoking and nonclear dyspepsia (Zullo et al, 2006).…”
Section: Sequential Therapymentioning
confidence: 99%
“…H. pylori infection is nearly 50-75%affected of the worldwide demography, in the developing countries 70% of people are affected, whereas the percentages little lower, (25-50%) in the developed countries (Safavi et al, 2016;Zhao et al, 2014). It is mainly attained earlier (about previously 10 years) and persist life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation